“They Will Crack Heads When the Communist Line Is Expounded”: Anti-Communist Violence in Cold War Canada - Luciuk, Kassandra (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2022)
This article examines anti-communist political violence in Canada during the early years of the Cold War. It specifically focuses on the Ukrainian Canadian community, one of the country’s most politically engaged and divided ethnic groups. While connected to an existing split within the community, acts of violence were largely committed by newly arrived displaced persons who were much more radical than existing anti-communist Ukrainian Canadians. Government and state officials tacitly, and sometimes even explicitly, sided with the perpetrators. This laxity toward the violence reveals how, in the early years of the Cold War, law and justice were mutable and unevenly enforced depending on the political orientation of those involved. In a broader sense, this article adds to an understanding of the multifaceted ways that anti-communism manifested itself in this period to define the acceptable parameters of political consciousness.